ANALISIS AKURASI METODE FUZZY TSUKAMOTO PADA SISTEM REKOMENDASI PEMILIHAN KAMERA - Setiyowati, Setiyowati; Deonardho, Yefri; Hasbi, Muhammad; Budiadi, Hasman (Jurnal Ilmiah SINUS, 2026)
Photography is one of the fields of visual communication that has many enthusiasts in Indonesia. The development of cameras has undergone many changes over time, making a variety of camera options and components available, which creates confusion for consumers who are buying the camera that best suits their needs. Tsukamoto’s fuzzy method is a component of soft computing. In the Tsukamoto method, each consequence of an IF-THEN rule must be represented by a fuzzy set with a monotonous membership function. The purpose of making the application “Camera Selection Recommendation System with Tsukamoto Fuzzy Method at Photography Shop” is to explain the tsukamoto fuzzy method as one of the methods of selection techniques with criteria and also provide recommendations for camera buyers according to the desired criteria in the hope that people who are unfamiliar with cameras do not make the wrong choice when they want to buy a camera according to their functions and needs. The 'wrong choice' in this context refers to a functional mismatch where a consumer acquires a device that lacks essential technical specifications for their specific use case such as low battery endurance for outdoor shoots or insufficient video resolution for professional content or conversely, investing in high-end features that remain underutilized, leading to inefficient resource allocation.